Foreword - Leveraging the HBCU Experience Globally (Comparative & International Education Series, 2021)
Historically Black Colleges and Universities (HBCUs) have evolved their own deep legacy of global engagement over the nearly two centuries since their founding.  Black educators and educational institutions, closely interwoven with Black religious institutions, have long connected with the African continent, the Caribbean, and even Europe as fertile, foreign spaces for collaboration and partnership.  Today’s HBCU cross-cultural programs and collaborations are rooted in the cosmopolitan connections that emerged in the periods of forced migration, enslavement and colonization.  This global element of the Black experience has been too often discounted and overlooked generally and, certainly, with respect to HBCUs that have consistently challenged the notion that they are exclusively local and domestic in their context and aspirations.